If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 55 = (3x + -1) * 5 Reorder the terms: 55 = (-1 + 3x) * 5 Reorder the terms for easier multiplication: 55 = 5(-1 + 3x) 55 = (-1 * 5 + 3x * 5) 55 = (-5 + 15x) Solving 55 = -5 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 55 + -15x = -5 + 15x + -15x Combine like terms: 15x + -15x = 0 55 + -15x = -5 + 0 55 + -15x = -5 Add '-55' to each side of the equation. 55 + -55 + -15x = -5 + -55 Combine like terms: 55 + -55 = 0 0 + -15x = -5 + -55 -15x = -5 + -55 Combine like terms: -5 + -55 = -60 -15x = -60 Divide each side by '-15'. x = 4 Simplifying x = 4
| -4-7/6 | | 15r^3+5r^2-120r= | | 19=7x-x+1 | | I=800*.09*3 | | 105/56 | | a^6+64=0 | | -6=-3r+2r | | -5(3-2x)(x)=-3x^2+2 | | -83=-5x-7x+1 | | C+19-4= | | 6(3x-1)(3x-1)+5=-17(3x+1) | | 3x+8x=2-5+5x+5x | | 5/6x-7/6=4 | | r=.066*3000(1-0.59*.066) | | 25s^2-81= | | 3(2y-7)=3 | | (4x^2+8x/4x+5)-(7x+5/4x+5) | | (x-4)^2/3=16 | | -3x+3+4x=5 | | 9k=2.34 | | 1/x+5/x-4=0 | | -6(x+9)-6+3x=25 | | b-26/17 | | 2(x-7)=5x-12 | | -10+7x+5x=-118 | | 13-28/x=4+8/x | | 4(x+7)=2x+31 | | 9(x-4)/3x | | 8.34x+41.7=83.4 | | (2/3)Y+(1/2(Y-3))=(Y+1)/4 | | 5(x+1)/25 | | 4x-50=190 |